Fast stratocumulus time scale in mixed layer model and large eddy simulation. (14th March 2014) - Jones, C. R.; Bretherton, C. S.; Blossey, P. N.
Abstract: A mixed layer model (MLM) and large eddy simulation (LES) are used to analyze the internal response time scales of a stratocumulus‐topped boundary layer (STBL). Three separate time scales are identified: a slow time scale associated with boundary layer deepening (several days), an intermediate thermodynamic time scale (approximately 1 day), and a fast time scale (6–12 h) for cloud water path adjustment associated with an internal entrainment‐liquid flux (ELF) feedback. The nocturnal DYCOMSII‐RF01 case study is used to establish and interpret the previously unidentified fast STBL adjustment time scale with the MLM. The role of the entrainment closure is investigated by repeating the analysis with several different closures. Nearly every closure considered exhibits a fast time scale. Perturbations are applied to the well‐mixed CGILS stratocumulus case in both MLM and LES in order to elicit a short time scale response. Purely radiative perturbations do not project strongly onto the fast scale, while perturbations to the free tropospheric humidity do. A 2K surface and atmospheric temperature perturbation also projects strongly onto the fast scale. We show that the ELF adjustment mechanism behind the fast time scale is responsible for much of the steady state liquid water path response in the perturbed case, acting as a cloud‐thinning feedback mechanism in a uniformly warmed climate. Key Points: We identify a fast Sc time scale due to entrainment‐liquid flux (ELF) feedback Fast time scale is corroborated by MLM, LES, and physical reasoning ELF adjustment acts as a cloud‐thinning feedback in uniformly warmed climate